The Impact of Story Completion Technique on Enhancing Speaking Proficiency among Extroverted and Introverted Students - Yun Angraeni Saputri; Nurnia Nurnia; Kamaluddin Kamaluddin (Halu Oleo University, 2023)
The utilization of story completion as a novel technique for teaching speaking skills in narrative text has shown promising results in enhancing students' oral proficiency. This study aimed to investigate the effectiveness of story completion on the speaking ability of both extroverted and introverted students at the Eighth-Grade level of SMPN 2 Kodeoha. Employing a quasi-experimental research design, the study selected students from two classes: Class VIII A, designated as the story completion group, and Class VIII B, serving as the control group receiving conventional instruction. Both groups covered the same topic during the study period. Data collection and analysis were conducted using Microsoft Excel. The findings revealed notable differences in speaking scores between the two groups. Specifically, the mean speaking score of introverted students in the story completion group surpassed that of their counterparts in the conventional group. Moreover, upon closer examination, both extroverted and introverted students in the story completion group demonstrated higher speaking scores compared to those in the conventional group. Furthermore, the results indicated that extroverted students outperformed introverted students in both groups in terms of speaking proficiency. These findings underscore the efficacy of employing story completion as a pedagogical tool for enhancing speaking skills, particularly among introverted students. Overall, the study sheds light on the differential impact of instructional methods on students' speaking abilities, highlighting the potential benefits of tailored approaches for diverse learner profiles.